Компьютерное моделирование осесимметричных течений жидкости в каналах сложной формы - Суворова, И. Г. (НТУ "ХПИ", 2004)
The paper considers theoretical principles of the R-functions method application to axisymmetric fluid in the channel of complicate form. The computer-based models of such fluid are created. Also the efficiency of one based on computation of the real channel are showed.
Keywords: движение вязкой жидкости; закон трения Ньютона; метод R-функций; числа Рейнольдса; функция тока; гидродинамические характеристики